English Student-Teachers’ Awareness of Communication Strategies and Their Implementation During Internship Program - Moh Taufik (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study aims to examine the use of Communication Strategies (CSs) by English language student teachers within a classroom setting. To achieve this, a qualitative research method involving document analysis was utilized. The analyzed documents consisted of video lesson studies from English education students participating in a 2024 educational internship program. Data collection involved: 1) selecting videos of model lesson study teachers from the internship schools for analysis, 2) the model teacher and their team reviewing these videos, 3) the model teacher and team engaging in group reflections and analyzing the use of communication strategies using a predefined list of CS types while providing example quotes, and 4) the team questioning the model teacher about the rationale behind using these strategies. The data analysis process included three concurrent activities: data condensation, data display, and conclusion drawing/verifying. The study's findings indicate that English education student teachers employed 16 different types of CSs during the internship program for classroom communication. These strategies include Message Abandonment, Message Reduction, Message Replacement, Approximation, Restructuring, Literal Translation, Code-switching, Omission, Self-repair, Other-repair, Comprehension Check, Asking for Repetition, Asking for Clarification, Expressing Non-understanding, Interpretative Summary, and Repetitions.